Deep reaction network exploration at a heterogeneous catalytic interface - Qiyuan Zhao; Yinan Xu; Jeffrey Greeley; Brett M. Savoie (Nature Communications, 2022)
This study demonstrates how reaction network characterization can be performed on heterogeneous catalytic surfaces predictively, rather than retrospectively, using automated exploration algorithms on an ethylene oligomerization exemplar reaction.